1980
DOI: 10.1021/i260076a014
|View full text |Cite
|
Sign up to set email alerts
|

Global Model of Countercurrent Coal Gasifiers

Abstract: This is a model of a fixed-bed coal gasifier in which CO, C02, K20 and H2 are assumed to be in thermodynamic shift equilibrium over a zone in which the primary gasification reactions occur. Exiting temperatures from this zone are in excess of 550 °C and the shift reaction is readily catalyzed by gas-borne impurities. Fresh coal is pyrolyzed in this gas stream and its gaseous products are added quantitatively to the shift gases. The final raw product gases thus calculated are close to experimental data from sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 6 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…Buekens and Schouters [30] have recommended use of equilibrium models for design of coal and biomass gasifiers, as these models give meaningful results with minimum parameters. Kosky and Floess [31] have found close correlation between product gas composition in oxygen or air blown fixed bed coal gasifier with that predicted using simple equilibrium model. Shand and Bridgwater [32] have reviewed thermodynamic models for downdraft gasifiers that incorporate feedstock composition, moisture, HHV, heat losses, excess oxidant and extent of shift reaction as parameter.…”
Section: Literature Reviewmentioning
confidence: 69%
“…Buekens and Schouters [30] have recommended use of equilibrium models for design of coal and biomass gasifiers, as these models give meaningful results with minimum parameters. Kosky and Floess [31] have found close correlation between product gas composition in oxygen or air blown fixed bed coal gasifier with that predicted using simple equilibrium model. Shand and Bridgwater [32] have reviewed thermodynamic models for downdraft gasifiers that incorporate feedstock composition, moisture, HHV, heat losses, excess oxidant and extent of shift reaction as parameter.…”
Section: Literature Reviewmentioning
confidence: 69%
“…However, it is known that thermodynamic equilibrium may not be achieved mainly because of the relatively low operation temperatures (product gas outlet temperatures between 750± 1000°C, Bridgewater, 1995), (Buekens and Schouters, 1984). Nevertheless, models based on thermodynamic equilibrium have been used widely (Buekens and Schouters, 1984;Kinoshita et al, 1991;Watkinson et al, 1991;Denn et al, 1979;Kosky and Floess, 1980;Kovacik et al, 1989;Cousins, 1978;Shesh and Sunavala, 1990;Shand and Bridgewater, 1984;Kilpinen et al, 1991). Watkinson et al (1991) demonstrated that discrepancies in comparison of equilibrium gas composition with experimental data may re¯ect unknown temperature gradients from the gasi®cation zone to the outlet zone.…”
Section: Introductionmentioning
confidence: 99%
“…9. Klosky and Floess 10 have also used equilibrium thermodynamic model for the prediction of product gas composition from air or oxygen‐blown fixed‐bed gasifier. Kovacik et al .…”
Section: Literature Review and Justification Of Present Studymentioning
confidence: 99%
“…Parametric sensitivity of moving bed coal gasifier was studied by Denn et al [9]. Klosky and Floess [10] have also used equilibrium thermodynamic model for the prediction of product gas composition from air or oxygen-blown fixed-bed gasifier. Kovacik et al [11] have used equilibrium models for the prediction of product gas composition from entrained flow and fluidized bed reactors.…”
Section: Literature Review and Justification Of Present Studymentioning
confidence: 99%